Cerebral arteriovenous malformations: Improved nidus demarcation by means of dynamic tagging MR-angiography - Essig, Marco; Engenhart, Rita; Knopp, Michael V.; Bock, Michael; Scharf, Johann; Debus, Jürgen; Wenz, Frederik; Hawighorst, Hans; Schad, Lothar R.; Kaick, Gerhard van (Magnetic resonance imaging, 1996)
Our purpose was to further improve the target volume definition for radiosurgical treatment of cerebral arteriovenous malformations (AVMs) by means of dynamic MRA (dMRA) using a blood bolus tagging sequence. We therefore compare this technique with 3D-TOF-MRA and transfemoral high resolution angiography in plain film technique. Twenty patients with angiographically proven cerebral AVMs were investigated by dMRA, TOF-MRA, and conventional angiography during the MR-assisted radiosurgical planning protocol. The patient's head was fixed in an MR-compatible stereotactic device. The different angiography techniques were evaluated by consensus of two radiologists. AVMs were characterized by the number and origin of feeding arteries, the maximum diameter of the AVM nidus, and the venous drainage pattern. Dynamic MRA was able to demonstrate the complete AVM characteristics and hemodynamics in 12 out of 20 patients. In three patients with an AVM nidus smaller than 1 cm in diameter, the technique could not reliably depict the malformation. Technical problems due to steel skrews and pins in the initially used stereotactic frame occured in five patients. Due to reduced vessel overlap and the lack of disturbances caused by formations with short T1 time, dMRA was superior to TOF-MRA in the detection and the exact localization of the AVM nidus in four patients. We conclude that dMRA is able to demonstrate reliably AVM characteristics and hemodynamics in AVMs with a nidus larger than 1 cm in diameter. Because of the improved demarcation of the AVM nidus, this technique may be a valuable adjunct to radiosurgery planning of cerebral AVMs.